Assessment of Green Practices in Sentra Timur Apartment, Jakarta Based on Greenship Rating of the Green Building Council of Indonesia - Aqil AZIZI; J RACHEL; Dicky SETIAWAN (International Journal of Environmental, Sustainability, and Social Science, 2023)
Before the Paris meeting on climate change, most United Nations member submitted their Intended Nationally Determined Contributions on carbon emission reductions by 2030. The Indonesian government needs to adjust its national policies and regulations to achieve its commitments. The residential building sector, in particular apartment buildings, plays an essential role in contributing to the country's energy-related carbon emissions profile. Therefore, this study aims to determine the extent to which apartments in Sentra Timur comply with the green building (GB) indicators, based on the standard of the Green Building Council Indonesia (GBCI). The analysis generates points that define a green building's predicate. Furthermore, the appropriate credit for Site Development, Energy Efficiency and conservation, Water Conservation, as well as Indoor Health and Comfort are 12 points out of 17, 16 points out of 26, 10 points out of 21, 16.5 points out of 26, respectively. The overall score is 54.5, with a percentage of 46.58%. Therefore, the Sentra Timur Apartment has been awarded a silver rating. After analyzing the collected data, recommendations were made on how each category can be improved to meet GB standards.